(untitled) (Annals of Medical Research, 2021)
Aim: Confirming the diagnosis and identifying the etiology are critical for the management of chronic obstructive pulmonary disease (COPD) exacerbation. There is limited use of hemogram and C-reactive protein (CRP) in distinguishing infectious or non-infectious in exacerbations. However, procalcitonin is more precious in making this distinction, although it is less accessible and more expensive. The aim of this study was to investigate the association between procalcitonin, CRP, hemogram parameters and ratios, and the efficacy of new hematological ratios in differential diagnosis in subjects with COPD exacerbation. Materials and Methods: Subjects admitted to our outpatient clinic with the diagnosis of COPD were retrospectively analyzed and divided into 2 groups: those with acute exacerbation (n=52) and those are stable (n=64). Neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR) and platelet-lymphocyte ratio (PLR) were calculated for both groups. Subjects were grouped according to NLR cut-off point determined by the ROC curve (NLR <3.03 and NLR ≥ 3.03) and were compared in terms of variables. Results: Comparing the values of NLR, PLR and MLR, all of these were significantly higher in the exacerbation group (p <0.001). A positive correlation with WBC, neutrophil count, NLR, PLR, MLR, RDW, PDW and a negative correlation with lymphocyte count, PCT and MPV were detected in the correlation analyzes between exacerbation rate and hemogram parameters. When NLR ≥ 3.03 (n = 63) and NLR <3.03 (n = 53) groups were compared it was remarkable that exacerbation rate and procalcitonin were found significantly higher in group with high NLR (p <0.001 and p = 0.02, respectively). However, there was no significant difference between two groups in terms of CRP values (p = 0.32). Conclusion: This study has shown that basic hematological parameters routinely examined in clinical practice can be used like those of sophisticated biomarkers in acute exacerbations of COPD.